2015
DOI: 10.1002/mrd.22528
|View full text |Cite
|
Sign up to set email alerts
|

Lack of protein kinase C‐delta (PKCδ) disrupts fertilization and embryonic development

Abstract: This study tested the function of protein kinase C delta (PKCδ) during fertilization and embryonic development using gene-knockout (Prkcd(-/-)) mice. Fertility analysis revealed that Prkcd(-/-) mating pairs produce significantly fewer pups per litter than wild-type pairs (P< 0.05), and exhibit a high incidence of embryonic loss post-implantation. Both Prkcd(-/-) male as well as Prkcd(-/-) female mice mated to Prkcd(+/+) controls also showed reduced litter sizes, with a selective loss of Prkcd-null pups. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…It also has been reported that the experiments with sperm from PKCδ KO male mice and oocytes from WT female mice resulted in lower fertilization rates and lower early cleavage rates [41]. However, in our study, results of in vitro fertilization with eggs from three WT females using one male PKCδ KO mouse spermatozoa showed no differences from WT male spermatozoa when comparing fertilization rates and developmental conditions up to two cells.…”
Section: Plos Onecontrasting
confidence: 69%
“…It also has been reported that the experiments with sperm from PKCδ KO male mice and oocytes from WT female mice resulted in lower fertilization rates and lower early cleavage rates [41]. However, in our study, results of in vitro fertilization with eggs from three WT females using one male PKCδ KO mouse spermatozoa showed no differences from WT male spermatozoa when comparing fertilization rates and developmental conditions up to two cells.…”
Section: Plos Onecontrasting
confidence: 69%
“…While loss of PKCδ has been reported to reduce fertility, post-natal development of PKCδ−/− mice appears to be normal (Ma, Baumann, & Viveiros, 2015), although subtle developmental phenotypes have been reported. For instance, we show a transient delay in mammary gland development in PKCδ−/− mice, including reduced ductal branching (Allen-Petersen et al, 2010).…”
Section: Biological Functions Of Pkcδmentioning
confidence: 99%
“…It is conceivable that the hyperactivation of Ras affects survival of spermatids and contributes to a higher sperm count yet lower quality sperm. Activation of ERK is associated with reduction in sperm quality [21] and alterations in sperm quality are known to reduce the number of offspring produced [41, 42]. The presence of abnormal spermatid morphology such as atypical residual bodies in the spermatids of Nf1 +/- mice further supports the hypothesis that Nf1 +/- mice produce lower quality sperm.…”
Section: Discussionmentioning
confidence: 99%